Recycling energy taxes: Impacts on a disaggregated labour market - Francesco Bosello; Carlo Carraro (Fondazione Eni Enrico Mattei (FEEM), 1999)
This paper analyses the costs and benefits of a fiscal reform designed to simultaneously increase environmental quality and employment. The investigation is carried out using an econometric general equilibrium model in which the labour market is unionised and segmented, i.e. in which demand, supply and the wages formation process for skilled and unskilled workers are explicitly modelled. This allows us to simulate the implementation in European countries of a harmonised carbon tax whose fiscal revenue in each country is re-cycled to reduce the gross wages of unskilled workers only rather than those of the whole labour force. This paper describes first the theoretical features of the segmented labour market which have been developed and then shows the estimates of the labour market equations. The effects of the double-dividend policy reform previously described are analysed and then compared with those of the traditional and simpler environmental fiscal reform in which the fiscal revenue is used to reduce the gross wages of all workers. We will show that (i) the "green" fiscal reform is more effective, in terms of employment gains, when the fiscal revenue is used to reduce gross wages of all employed workers as a mild substitutability relationship among skilled and unskilled workers is identified, (ii) the employment dividend increases when the tax reform is carried out in a co-operative way i.e. equalising through international co-operation its marginal benefits and costs among countries, (iii) if an "employment double dividend" is feasible in the short-run, a trade-off employment/environment remains in the longer term.
Keywords: H0; H2; H3; 330; Double dividend; environmental fiscal reform; environmental modelling; Energiesteuer; Beschäftigungseffekt; Steuerwirkung; Simulation; Theorie